HYBRID FIXED POINT THEOREMS WITH PPF DEPENDENCE IN BANACH ALGEBRAS WITH APPLICATIONS - C.dhage, B. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
In this paper, two hybrid fixed point theorems with PPF dependence in Banach algebras are proved and they are then applied to some hybrid functional differential equations of delay and neutral type for proving the existence of PPF dependent solutions.